Evaluating the Performance of Pedestrian Traffic on signalized intersections according to the methodology of HCM 2016 in the city of latakia - الخنسه, حنان; أكرم رستم (Latakia University Journal -Engineering Sciences Series, 2022)
The research aims to assess the reality and performance of pedestrian movement at the intersection organized by a traffic light according to the 2016 HCM methodology by evaluating the pedestrian gathering area for each corner of the studied intersection in order to know the level of service for pedestrians and propose the required solutions. The studied intersection in the city of Latakia was identified, which is the intersection of Abdul Rahman Al Ghafiqi Street with Shukri Al-Quwatli Street. and the traffic data collection (vehicle flow rate and pedestrian flow rate) and engineering data (sidewalk width, lane width, lane length, number of lanes) the light signal data (light signal cycle time, green and red time) and then applying the computational steps. The results showed after applying the steps of the methodology that the condition of most corners of the intersection needs to adjust the lane to avoid collisions, except for the southwestern corner, there is a repeated need to adjust the lane.